The Challenges of Chastity, Self-Restraint, and Abstinence in the Digital Age: A Quranic, Hadith, and Psychological Study of the Effects of Social Media - Klaina, Mekki; Kmichou, Halima (Darul Yasin Al Sys, 2025)
The significance of this topic lies in the role of religious awareness in strengthening ethical values among individuals and communities, with its profound impact on shaping social and moral concepts that contribute to the construction of a stable society. This research seeks to explore the extent to which religious awareness influences individuals' behaviors and perceptions of ethical values, as well as the role of various media in reinforcing these values. The research addresses the question: Can religious awareness bring about real, tangible changes in individuals' behaviors and their perceptions of ethical values in the modern world? The methodology used in this study is descriptive-analytical, focusing on examining Quranic verses and prophetic hadiths related to the topic in order to understand their implications in safeguarding individuals and communities psychologically, healthily, socially, economically, and politically. Data were collected through surveys and opinion polls to assess the impact of religious awareness on ethical values. The key findings highlight that religious awareness plays a pivotal role in promoting ethical values, confirming that individuals exposed to religious content adopt more positive behaviors and values in their daily lives. The study also reveals that various media platforms, such as religious sermons and videos, significantly contribute to shaping and altering ethical attitudes. In conclusion, the research emphasizes the importance of religious guidance as an effective tool for achieving moral change and reinforcing values within society.